Accuracy of national mortality codes in identifying adjudicated cardiovascular deaths - Harriss, Linton R.; Ajani, Andrew E.; Hunt, David; Shaw, James; Chambers, Brian; Dewey, Helen; Frayne, Judith; Beauchamp, Alison; Duvé, Karen; Giles, Graham G.; Harrap, Stephen; Magliano, Dianna J.; et al. (Australian and New Zealand journal of public health, 2011)
This study investigated the sensitivity and specificity of the national mortality codes in identifying cardiovascular disease (CVD) deaths and documents methods of verification. A 12‐year retrospective case ascertainment of all ICD‐coded CVD deaths was performed for deaths between 1990 and 2002 in the Melbourne Collaborative Cohort Study, comprising 41,528 subjects. Categories of non‐CVD codes were also examined. Stratified samples of 750 deaths were adjudicated from a total of 2,230 deaths. Expert panels of cardiologists and neurologists adjudicated deaths. Of the 750 deaths adjudicated, 582 were verified as CVD [392 coronary heart disease (CHD) and 92 stroke] and 168 non‐CVD. Estimated sensitivity and specificity of national mortality codes for identifying specific causes of death were: CHD 74.2% (95% CI: 69.8–78.5%) and 97.6% (96.0–99.2%), respectively; myocardial infarction 59.9% (50.9–69.0%) and 94.2% (92.4–96.0%), respectively; haemorrhagic stroke 58.9% (46.0–71.7%) and 99.8% (99.4–100.0%), respectively and; ischaemic stroke 38.7% (20.5–56.9%) and 99.9% (99.6–100.0%), respectively. Misclassification was most common for deaths with primary ICD codes for endocrine‐metabolic and genito‐urinary diseases. National mortality coding under‐estimated the true proportion of CHD and stroke deaths in the cohort by 13.6% and 50.8%, respectively. Misclassification of cause of death may have implications for conclusions drawn from epidemiological research.